The Effect Of Resistance Band Training And Ankle Weight Training On The Front Kick Speed Of Pencak Silat Athletes - Ahmad Alghifary Dwi Mahendras; Ranu Baskora Aji Putra (Universitas Negeri Semarang, 2026)
This study aims to determine the effect of resistance band training and ankle weights on the front kick speed of pencak silat athletes at the Tri Gerak Sakti in North Jakarta. This study used a quantitative method with a quasi-experimental two-group pretest-posttest design. The study sample consisted of 12 female athletes divided into two groups, namely the resistance band training group (n = 6) and the ankle training group (n = 6). The instrument used was a 10-second front kick speed test. Data were analyzed using the Shapiro-Wilk normality test, homogeneity test, and paired sample t-test hypothesis testing with the help of SPSS version 22 at a significance level of 0.05. The results showed that both groups experienced an increase in average scores from pretest to posttest. The resistance band group increased from a mean of 20.33 to 23.67, while the ankle group increased from a mean of 19.83 to 22.67. The hypothesis test showed a significance value of 0.000 <0.05 in both groups, so that resistance band training and ankle weights had a significant effect on increasing front kick speed. Furthermore, resistance band training provided greater gains than ankle weights. Therefore, both training methods can be used in pencak silat training programs to improve the biomotor component of an athlete's front kick speed.